The effect of different cementation techniques on the amount of remaining excess cement depending on the crown-abutment margin level - Đorđević Aleksandar; Todić Jelena; Simić Sanja; Lazić Dragoslav; Vlahović Zoran; Šubarić Ljiljana (Vojnosanitetski Pregled)
Background/Aim. One of the disadvantages of the cement-retained fixed implant-supported restorations is the residual cement, which is found on the superstructure after the cementation procedure and has been identified as a risk factor for the occurrence of peri-implantitis. The aim of the study was to examine the influence of cementation techniques on the amount of residual cement at different levels of demarcation of the abutment in relation to the gingiva in the process of cementing restorations on implants. Methods. The research was conducted in in vitro conditions on casts obtained after implant placement. The abutments are milled at the level of the gingiva, 1.5 mm subgingivally and 3 mm subgingivally. Zirconium dioxide ceramic restorations were cemented using a standard cementation technique, a cementation technique using Teflon tape, and a precementation method using a silicone replica of the abutment and a 3D printed replica. The amount of residual cement was measured by photograph analysis. Adobe Photoshop was used for software analysis of photographs and determination of cement surface. Statistical data processing was per-formed in the SPSS program, and the Kruskal-Wallis test was used for data analysis. Results. A comparative analysis of the effectiveness of cementation techniques at the gingival margin level revealed a statistically significant difference in the amount of residual cement in relation to the cementation technique (p < 0.001). Analyzing the cementation technique effectiveness at the level of the finish line, 1.5 mm subgingivally, it was established that there was a statistically significant difference in the amount of residual cement compared to the cementation technique (p = 0.001). Comparing the effectiveness of cementation techniques at the 3 mm subgingival finish line level, it was established that there was a statistically significant difference in the amount of residual cement compared to the cementation technique (p < 0.001). Conclusion. Subgingival localization significantly affects the amount of residual cement in fixed prosthetic restorations on implants. Applying precementation techniques significantly reduces the amount of residual cement.